The history of the tetracyclines - Nelson, Mark L.; Levy, Stuart B. (Annals of the New York Academy of Sciences, 2011)
The history of the tetracyclines involves the collective contributions of thousands of dedicated researchers, scientists, clinicians, and business executives over the course of more than 60 years. Discovered as natural products from actinomycetes soil bacteria, the tetracyclines were first reported in the scientific literature in 1948. They were noted for their broad spectrum antibacterial activity and were commercialized with clinical success beginning in the late 1940s to the early 1950s. The second‐generation semisynthetic analogs and more recent third‐generation compounds show the continued evolution of the tetracycline scaffold toward derivatives with increased potency as well as efficacy against tetracycline‐resistant bacteria, with improved pharmacokinetic and chemical properties. Their biologic activity against a wide spectrum of microbial pathogens and their uses in mammalian models of inflammation, neurodegeneration, and other biological systems indicate that the tetracyclines will continue to be successful therapeutics in infectious diseases and as potential therapeutics against inflammation‐based mammalian cell diseases.